FOR REVENGE: THE PHENOMENON OF EMO MUSIC PERFORMANCES AND AUDIENCE EMOTIONS - Ardini, Ni Wayan; Wijaya, I Nyoman Cahyadi; Mudana, I Gede (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This research was conducted for the purpose of identifying the character of emo (emotional hardcore) music performances and their relationship to the emotional situation of the audience watching them, especially in the case of a music group in Indonesia named for Revenge. This qualitative research, which relies on document studies, observations and interviews, found that this underground group with an emo (emotional hardcore) character, with themes of inner conflict, suffering and rebellion, especially in matters of love, deserves to label itself as "for revenge” or “untuk balas dendam” in Indonesian. Apart from being musically aesthetic, the emo lyrics created in many cases are truly capable of piercing the deepest hearts of audiences who have experienced love problems. In today's era of social media, this group is favored by a fairly large segment of the youth market. This means that in Indonesia for Revenge has increasingly succeeded in blurring the boundaries between underground entities and the popular music industry.